A review: Hydrotalcite layers as protective coatings on zinc and zinc alloys - Thi Xuan Hang, To; Pham , Thu Thuy; Nguyen, Thuy Duong; Olivier , Marie-Georges (Vietnam Journal of Science and Technology, 2024)
In recent years, there has been significant research and development in area of corrosion prevention and protection, focusing on hydrotalcites layers on zinc and zinc alloys due to their distinct attributes, such as their capability to accommodate anions, ability to exchange anions, capability  for structural memory, and its resistance to barriers. This review primarily aims to summarize findings related to how the formation of HT layers on zinc and zinc alloys is affected by various synthesis conditions. Besides, we compared and deliberated upon HT layers' anti-corrosion mechanism and corrosion protection.